POLA LARIK DALAM ANTOLOGI PUISI MATAHARI TANPA KAKI - Rani Pravita; Charlina Charlina; Syafrial Syafrial (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study titled Pattern Array In The Antology Poetry Of Matahari Tanpa Kaki. The background of this research is that researchs want to see how the students bulid a series of poems. The purpose of this study is to find out the tendency of the array pattern in the Antology Poetry Of Matahari Tanpa Kaki. This research is a descriptive qualitative research that describes the result of the research carried out. Based on research, there are 16 phrases, with the most dominant pattern being the noun + verb pattern. The clause with the most dominant pattern is the s + p pattern and 10 sets with the most dominant pattern are the noun pattern. The tendency of the arrangement pattern in the Antology Of The Poetry Of Matahari Tanpa Kaki is in form of clauses.Key Words: Trend, pattern, array, anology of poetry